Pengaruh Beban Kerja, Pelatihan Audit Kecurangan Dan Tekanan Waktu Terhadap Kemampuan Auditor Dalam Mendeteksi Kecurangan (Studi Empiris Pada Kap Padang) - Rahmaita .; Ella Maisyarah (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This research aims to analyze the effects of workload, fraud audit training, and time pressure on the auditor's ability to detect fraud at Public Accounting Firms (KAP) in Padang. The study is motivated by recent audit failures and the increasing complexity of financial fraud cases. Using a quantitative approach and causal-explanatory research design, involving Public Accounting Firm (KAP) auditors in Padang City as a sample analyzed using multiple linear regression. The results of the simultaneous test (F-test) show that all independent variables collectively influence the auditor's fraud detection ability. Specifically, the partial test (t-test) reveals that fraud audit training has a significant positive impact on improving an auditor's ability to identify fraud. However, workload and time pressure were found to have no significant effect on fraud detection capabilities in this specific context. These findings suggest that continuous professional training is more critical than situational pressures in determining audit quality. Public Accounting Firms are encouraged to prioritize structured fraud training programs to enhance their auditors' technical skills and professional skepticism.